The grammar structure of religious intertextuality structures used by Al-Jahez in modern linguistics, especially the Message of Nostalgia - Al- Shammari, Awad bin Baik (Arab Journal for Sciences and Research Publishing, 2018)
This study aims at revealing the mechanisms of religious intertextuality used by Al-Jahez in his book “The Messages”, especially the Message of Nostalgia. The student discusses definitions that are linguistically similar. That is: structural level, textual linguistics, textual criteria, and intertextuality in general and religious intertextuality in particular. In addition, it aims at presenting the most prominent roles of textual linguistics, intertextuality, religious intertextuality, together with finding the linguistic evidences for the structures of the religious intertextuality in the message of Al-Jahez” Nostalgia” with full explanation and analysis to this message depending on the methodology of structural level which includes the sciences of both syntax and morphology.
Keywords: Textual linguistics; the syntactic level; religious intertextuality; Intertextuality